Discourse Devices and Communicative Functions in Doctorpatient Verbal Interactions in Two Federal Teaching Hospitals in Nigeria (2016)
Discourse devices are the linguistic tools employed to address inherent problems in conversation for health purposes. Doctor-patient verbal interactions face major problems in clinical discourse due to differences in linguistic, sociolinguistic, cultural backgrounds as well as professional and communicative styles of doctors and patients. Pragmatic and sociolinguistic studies on doctor-patient verbal interactions have observed relevant socio-psychological and contextual factors, but with little attention on the deployment of discourse devices aimed at solving specific communication problems in this setting. This study, therefore, explored language use in doctor-patient interactions with a view to discovering specific discourse devices deployed to enhance diagnostic communication at the University College Hospital (UCH), Ibadan and University of Ilorin Teaching Hospital (UITH), Ilorin. The study adopted a synthesis of Brown and Levinson‟s politeness and M.A.K Halliday‟s Systemic Functional Linguistics as framework. One hundred tape recordings of doctor-out-patient interactions were made at UCH, Ibadan and UITH, Ilorin in 2013. The two hospitals were selected because they are the leading hospitals in the study locations (South-West and North-Central geo-political zones of Nigeria). Fifty of them were purposively sampled based on their strategic content (twenty-five from each hospital). The texts were transcribed, the discourse devices there-in were identified and the data were subjected to discourse analysis. Twelve discourse devices were dominant in the data. Doctors employed phatic communion for opening consultations; direct questions and indirect questions for diagnosis; face-threatening acts for presenting diagnosis politely; language switch for explicitness, informativity and mutuality; rapport expressions, for cordiality, solidarity and open communication; and religious belief for encouragement and solidarity. Counselling was employed to guide the patients on how best to handle their health. The patients employed answering for response to queries; closing of conversations for terminating consultations; repetition for emphasis; and circumlocution for communicating medical information. Interrogatives were employed for eliciting information (“Why did you come this morning?”). Declaratives were employed for providing information (“I have a problem with my teeth”). Language switch, realised by alternate use of English and Yoruba, was employed for clarity (“E ti wa tele ni Monday”), meaning: „You came here on Monday‟. Rapport expressions, realised by social questions, were deployed for cordiality (“What names do your friends call you?”). „Sorry‟ is a culture-bound expression used for empathy and sympathy. Imperatives were employed for giving directives (“Buy these drugs”). Some of the observable problems exhibited the possibility of doctors upsetting patients who engaged in injurious health practices. There are insignificant differences in the frequency of occurrence of the discourse devices employed at the University College Hospital, Ibadan, and University of Ilorin Teaching Hospital, Ilorin. For instance, UCH doctors employed rapport expressions 101 times (7.2%), while those of UITH employed them 92 times (6.63%). Discourse devices were deployed for addressing specific communication and health problems during diagnosis at the University College Hospital, Ibadan and University of Ilorin Teaching Hospital, Ilorin. Awareness of these, therefore, is important for a better understanding of diagnostic discourse in doctor-patient verbal interactions in the Nigerian context.